New record for Lymnaea neotropica (D'Orbigny 1835) in Argentina, with a detailed analysis of its morphology and molecular characteristics - Pujadas, Julieta Marina (2015)
We report for the first time the presence of Galba neotropica in Santa Fe province, Pampean Argentina. Until the present work, the identity of the intermediate host of Fasciola hepatica in this region, the most important livestock production area of Argentina, was unknown. This report extends the geographic distribution of G. neotropica and is the first to provide molecular and morphological information on this species in Argentina. During summer 2013, snails were collected on private livestock farms with high prevalence of fasciolosis in cattle. Specimens were identified by using the nuclear sequences of the internal transcribed spacers ITS-1 and ITS-2, the shell and the shape and size of the male reproductive organs. Molecularly, ITS-1 and ITS-2 nuclear sequences exhibit 100% nucleotide identity with G. neotropica from Lima, Peru. Morphologically, G. neotropica from Santa Fe province was indistinguishable from Galba viatrix and Galba cubensis, the other two cryptic species within this South American group of lymnaeids. The combination of molecular and morphological analyses is strongly recommended to identify lymnaeids at species level. The identity of the intermediate host and the subsequent knowledge of its susceptibility, behaviour, distribution, ecology and biology are important components in developing effective measures to control fasciolosis.